Strategi Komunikasi Korporasi untuk Meningkatkan Kepuasan dan Kualitas Produk Labbaik Chicken - Rini Rusnawati; Fiqri Nur Zulhakim; Gita Belaroza; Bunga Astri Cahya Nabiyina; Riska Ferdiana (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to analyze in depth the role of corporate communication strategies in enhancing customer satisfaction and maintaining product quality at Labbaik Chicken, a company operating in the fast food industry. In the context of the digital era and the Fourth Industrial Revolution, effective communication strategies are crucial for strengthening brand image and maintaining competitiveness in an increasingly dynamic market. Corporate communication serves not only as a tool for delivering information but also as a bridge to build long-term relationships with customers. This research employs a qualitative approach through literature review to explore relevant communication theories and link them to factors that influence customer satisfaction and product quality. The findings reveal that good, transparent, and responsive communication from the company can enhance customer trust, foster loyalty, and create a positive customer experience. Furthermore, consistent product quality that aligns with customer expectations—in terms of taste, presentation, and service—has a significant impact on customer satisfaction and purchasing decisions. Therefore, companies need to implement integrated communication strategies alongside product quality management to create added value and differentiation in the market. The conclusion of this study highlights that an appropriate corporate communication strategy is one of the key factors in increasing customer satisfaction and strengthening the company’s position and reputation in the competitive fast food industry.